2019
DOI: 10.1038/s41419-019-1635-9
|View full text |Cite
|
Sign up to set email alerts
|

ZCCHC10 suppresses lung cancer progression and cisplatin resistance by attenuating MDM2-mediated p53 ubiquitination and degradation

Abstract: The activation of p53 tumor suppressor is essential for preventing abnormal cell proliferation and carcinogenesis. ZCCHC10 was previously identified as a potential p53-interacting partner in a yeast two-hybrid screen, but the interaction in cells and its subsequent influence on p53 activity and cancer development have not been investigated. In this paper, we demonstrate that ZCCHC10 expression levels are statistically lower in lung adenocarcinoma tissues than the corresponding adjacent noncancerous tissues, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 29 publications
1
20
0
1
Order By: Relevance
“…Protein ubiquitylation is initiated by enzymatic cascades that involve E3 ubiquitin ligases (15). RNF180 is an E3 ubiquitin ligase that serves a key role in the function of the ubiquitin-proteasome system by determining the specificity and timing of ubiquitination and subsequent degradation of its substrates (16). RNF180 is either downregulated or absent in different types of cancer, and is regarded as a suppressor gene.…”
Section: Discussionmentioning
confidence: 99%
“…Protein ubiquitylation is initiated by enzymatic cascades that involve E3 ubiquitin ligases (15). RNF180 is an E3 ubiquitin ligase that serves a key role in the function of the ubiquitin-proteasome system by determining the specificity and timing of ubiquitination and subsequent degradation of its substrates (16). RNF180 is either downregulated or absent in different types of cancer, and is regarded as a suppressor gene.…”
Section: Discussionmentioning
confidence: 99%
“…23 ZCCHC10 bound to and stabilized p53 by impairing the binding relation between p53 and MDM2, and the p53 inhibitor pifithrin-α weakened the impacts of ZCCHC10 restoration on p53 pathway, cell cycle and apoptosis in lung cancer. 24 Our data demonstrated that specific inhibition of p53 by The data was performed as means ± SD of three independent experiments. One-way ANOVA was used to compare the mean of samples among multiple groups, followed by Tukey's multiple comparisons test.…”
Section: Dovepressmentioning
confidence: 51%
“…MDM2, as a negative regulator of p53, can bind to p53 to limit its function, and ubiquitinate p53 to promote degradation 22–24 . MDM2 maintains the tumor characteristics of lung cancer via suppressing the function and expression levels of p53 43–46 . For example, Cai et al .…”
Section: Discussionmentioning
confidence: 99%